Jatropha mutabilis, a new source of vitexin: HPLC quantification and pharmacological evaluation. Issue 24 (17th December 2021) - Costa, Eliatania Clementino; Menezes, Pedro Modesto Nascimento; Silva, Fabrício Souza; Ribeiro, Luciano Augusto de Araújo; Rolim, Larissa Araújo; Araújo, Edigênia Cavalcante da Cruz; Nunes, Xirley Pereira
Abstract: Jatropha mutabilis (Pohl) Baill is an endemic species of the Caatinga biome, little studied in terms of chemical composition. The objective of this work was to develop an analytical methodology to quantify vitexin in the ethanolic extract of J. mutabilis and to evaluate the expectorant and antitussive activities in mice. The expectorant activity was performed by measuring the phenol red obtained from the bronchoalveolar fluid in animals and the antitussive activity was evaluated by the cough method induced by citric acid (0.4 M). The method developed by HPLC–DAD proved to be simple, linear, precise, accurate, robust and specific. Besides, both vitexin (0.2, 1 and 5 mg/kg) and the extract of J. mutabilis (20, 102, 510 mg/kg) showed efficacy in decrease cough and increase aqueous mucus in mice, but vitexin was more potent. Lastly, the identification of vitexin opens the possibility of new studies for J. mutabilis . Abstract : UF0001